Pengaruh Persepsi Kemudahan, Persepsi Manfaat, dan Keamanan terhadap Minat menggunakan melalui Kepercayaan sebagai Variabel Intervening pada E-Wallet Flip di Kota Bekasi - Tri Puji Handayani; Nova Anggrainie (Journal Economic Excellence Ibnu Sina, 2024)
The development of technology has brought many changes, especially in the field of digital technology. One of the innovations of this development is Financial Technology or fintech. Fintech introduced electronic wallets or e-wallets, for example Flip. By using trust as an intervening variable, this study attempts to investigate the influence of perceptions of ease, benefits, and security on the interest in using Flip e-wallets in Kota Bekas. This study provides respondents with an online questionnaire to generate primary data for further analysis. Respondents were selected from a non-probability sampling method with a purposive sampling technique, resulting in 175 respondents with 35 statements. The research findings show that perceptions of ease, benefits, and security influence the interest of Kota Bekas residents in using Flip e-wallets. In addition, the level of trust in Flip e-wallets in Kota Bekas is also influenced by these three factors. Trust acts as an intervening variable to moderate the impact of views of ease of use, benefits, and security on the interest in using Flip e-wallets, where the findings prove that trust influences people's desire to use Flip e-wallets in Kota Bekasi.